An Empirical Analysis of the Factors Influencing the Rise of Single-Parent Households in Anambra State - Chiamaka Pamela Uchendu; Hendra Prasetyo (PT. Altaf Publishing Corp, 2026)
An evaluation of the socio-economic, relational, and demographic drivers of family instability forms the core of this investigation. A survey research design was adopted to study a population of 3,385 single parents in Anambra State. Using the Taro Yamane technique and multi-stage random sampling, a representative sample of 358 respondents was selected across three local government areas. Data were collected via a Google Form using the structured Child Rearing and Single Parenting Scale, which was face-validated by three experts and yielded high Cronbach's alpha reliability coefficients. Analysis was performed using SPSS, employing mean, standard deviation, and t-test statistics at a 0.05 significance level. The survey results show that respondents generally agree on the identified reasons for single parenting, yielding a grand mean of (2.84) and a standard deviation of (1.13). Unplanned pregnancies emerged as the most prominent factor with a mean of (3.24), followed closely by educational disparities at (3.13) and extramarital affairs at (3.00). In contrast, incompatibility with a partner's family was rejected with a mean of (2.44). The null hypothesis was rejected due to a significant difference in perceptions between the (97) male respondents who had a mean of (2.567) and the (261) female respondents who had a higher mean of (2.942). The study concludes that the expansion of single-parent households is productively tied to a network of structural and relational constraints rather than isolated cultural shifts.